Antinociceptive Effects of Oleuropein from Olea europaea L. Fruits - Hidayat Ur, Rahman (J-Stage, 2022)
Pain is a complex, unpleasant sensation caused by tissue damage, involving nociceptors, neural pathways, and brain processing. Its mechanisms include neurotransmitter imbalances, ion channel dysfunction, and impaired pain regulation. Current management combines medications such as NSAIDs, physical therapy, and psychological support, but side effects limit their use. This has spurred interest in safer natural alternative, such as oleuropein, a bioactive compound from Olea europaea L. with demonstrated anti-inflammatory and analgesic properties in traditional medicine. Integrating in-silico and in-vivo approaches, this present study, characterized oleuropein’s antinociceptive mechanisms and efficacy. Molecular docking analysis demonstrated strong binding affinities with opioid -8.62 kcal/mol, Transient Receptor Potential Vanilloid 1 -8.45 kcal/mol, Nitric Oxide Synthase 8.38 kcal/mol, muscarinic receptor -7.68 kcal/mol, ATP-sensitive K+ channel -6.88 kcal/mol, glutamate receptors -6.87 kcal/mol, suggesting multi-target mechanisms of action. In-vivo evaluations using thermal and chemical pain models revealed significant dose dependent analgesic effects. The formalin test showed 58.02-68.77% reduction in paw licking duration during both neurogenic (0-5 min) (p<0.001) and inflammatory (15-30 min) (p<0.001) phases at 100 mg/kg of oleuropein. Acetic acid-induced writhing was inhibited by 68.00% (p<0.001), while capsaicin-induced nociception showed 61.45% reduction (p<0.001). Glutamate tests revealed a biphasic U-shaped response, with maximal effect 51.34% inhibition (p<0.001). Mechanistic studies indicated that oleuropein's effects were partially but significantly reversed by naloxone, L-arginine, atropine, and glibenclamide, suggesting involvement of multiple pathways. In conclusion, the combined computational and experimental results demonstrate that oleuropein exerts robust antinociceptive effects through a unique multi-target mechanism involving opioid, cholinergic, glutamatergic, and TRPV1 systems, along with nitric oxide and KATP channel pathways. These findings position oleuropein as a promising natural alternative for pain management, with potential advantages over single-target synthetic analgesics. The study provides comprehensive evidence for oleuropein's dose-dependent efficacy across diverse pain models while elucidating its complex pharmacological profile, supporting further development as a novel analgesic agent.